The production of n-nitrosamines by gut bacteria - Phakathi, Madaliso (My University, 2020)
Cancer is one of the leading causes of morbidity and mortality worldwide. Gastrointestinal cancers have increased in prevalence. Studies have shown that cancer risk increases with exposure to carcinogenic compounds which can be found in the environment and in food. Nitrosamines are an example of such carcinogens, with in vivo studies in animal models demonstrating exposure to nitrosamines results in the development of particular cancers and the associations between nitrosamine exposure and cancers in humans. Nitrosamines are formed from nitrites, a common food preservative, and amines. It is now realized that micro-organisms may facilitate the production of nitrosamine compounds, with the gut microbiome playing a significant role. We therefore investigated whether or not the gastric inhabiting bacterium associated with gastric cancer, Helicobacter pylori alone, or Bacillus cereus and the combination of these, were able to produce nitrosamines. Strains of H. pylori and a reference strain of B. cereus were cultured in the presence of precursors to nitrosamine compound formation, nitrites, nitrates, a secondary amine alone, or in combination, in a standard reaction assay. Samples were extracted and analyzed for nitrosamine formation using gas chromatography with detection and identification by mass spectrometry. Although particular nitrosamine compounds were only produced by the individual bacteria, the important finding was that many more nitrosamines were also produced, and some at significantly elevated concentrations, by culturing H. pylori in supernatant of B. cereus. Many of these nitrosamines have been implicated in cancer formation. Cancer formation has been attributed to many different factors and the production of nitrosamines through microbial actions, specifically the combination of H. pylori and B. cereus, may be of relevance in gastrointestinal cancers. Further studies, including testing supernatants in animal models are required to confirm the findings of this study.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2020